HIV/AIDS Knowledge, Attitudes and Practices among Truck Drivers in Burkina Faso. - Gnimbar PODA Ghislain; Sondet SANON Guillaume (Journal of Clinical Research In HIV AIDS And Prevention, 2015)
Objective: Human immunodeficiency virus (HIV) /acquired immune deficiency syndrome (AIDS) affect all levels of society and drivers are considered as vectors of HIV transmission because of the mobility of their work. The aim of this study was to assess struck drivers’ knowledge, attitudes and practices on HIV and AIDS in Burkina Faso. Methods: Quantitative method and cross-sectional survey using questionnaire with Cronbach’s alpha 0.76 were used in this study. SPSS, version 18.0 was used for analysis. P-values ≤ 0.05 were considered statistically significant. Results: 150 truck drivers participated in the study with a mean age of 38.71 years (SD=8.87), and ranged from 25 to 68 years old. It was observed that misconceptions about HIV transmission are quite prevalent among truck drivers. About 61 (40.7%) felt that AIDS can be transmitted by sharing meals, 35 (23.3%) stated that it can be spread by mosquito bite and 65 (43.3%) were of the opinion that AIDS can be transmitted by using same toilet and cloths. High-risk behavior was established in the study. 78% have other sexual partners besides their wives and 34% often visit sex workers in which 26 % had unprotected sex with sex workers. Alcohol seems to have a big role in their sexual behavior; thus 22 % of truck drivers declare drink alcohol before sex. There were significant association in demographic factors and knowledge, attitude and practice. Conclusion: The study findings underline the negative risk behaviors of truck drivers. Safe sex and use of condom have to be promoted through education program among truck drivers in Burkina Faso.
Keywords: Truck driver